Students’ interpersonal skills and its association with their academic achievement in secondary school of Pakistan - Nisar Abid; Aqeela Samuel; Rizwan Ali; Almas Shoaib; Waqar Younas Warraich (Institute of Advanced Engineering and Science, 2022)
The educational productivity theory directed that students’ variables affect their performance. Therefore, this descriptive correlational study was designed to examine students’ interpersonal skills and its association with their achievement. There were 3,200 high school students participated in this study, selected from 80 high schools of Punjab through multistage random sampling technique. The Interpersonal Skills Scale (ISS) was adapted from DiPerna and Elliott’s Academic Competence Evaluation Scales-Student form (ACES-Student). ISS demonstrated a good internal consistency (coefficient alphas=0.819 and composite reliability=0.845). The results exhibited that students have a competent level of interpersonal skills. Moreover, a statistically significant difference was found in female and male students’ perceptions about interpersonal skills, while female have more interpersonal skills than male. Furthermore, ANOVA results concluded that administrative division (location) influences students’ perception of interpersonal skills. It is concluded from the correlational analysis that students’ interpersonal skills are indirectly associated with their achievement because a negative weak relationship was found in students’ interpersonal skills and their achievement as r=0.031, p=0.081. It is suggested that teachers may promote interpersonal skills by integrating cooperative and collaborative learning strategies into their classrooms.